2014
DOI: 10.1186/1752-1947-8-79
|View full text |Cite
|
Sign up to set email alerts
|

Unusual trichobezoar of the stomach and the intestine: a case report

Abstract: IntroductionTrichobezoars are an infrequent form of bezoar found in the stomach or intestine, created from ingested hair. This condition has been well described in the surgical literature, but less reported in psychiatry.Case presentationWe describe the case of an 18-year-old Middle Eastern Caucasian woman with trichotillomania who presented to our emergency department with a history of central abdominal pain associated with vomiting and constipation for five days. An examination showed a trichobezoar requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Trichobezoar is a rare condition presenting in just 0.06–4% of the population [ 1 ] defined as a mass of swallowed hair in the stomach [ 1 , 2 ]. Due to the smooth and indigestible nature of hair, when swallowed it accumulates in the gastric mucosa and over time it mixes with food and mucus, becoming compacted and forming a solid mass known as a trichobezoar [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichobezoar is a rare condition presenting in just 0.06–4% of the population [ 1 ] defined as a mass of swallowed hair in the stomach [ 1 , 2 ]. Due to the smooth and indigestible nature of hair, when swallowed it accumulates in the gastric mucosa and over time it mixes with food and mucus, becoming compacted and forming a solid mass known as a trichobezoar [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bezoars are concretions of indigestible matter that accumulate in the gastrointestinal tract. Trichobezoars, specifically, are defined as masses of swallowed hair usually in the stomach [ 1 , 2 ] due to the smooth and indigestible nature of hair which when swallowed accumulate in the rugae of the stomach and over time, mixing with food and mucus, they become compacted and form solid masses. Most commonly, the bezoars produce obstructive symptoms but rarely may cause ulceration and even bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons should, therefore, examine the entire gastrointestinal tract to achieve complete elimination of trichobezoars and avoid secondary intestinal obstruction due to satellites. 5 In the present case, a laparoscopic approach was considered to be inappropriate, as CECT revealed gastric and multiple intestinal hair masses and remarkable small bowel dilatation. Moreover, intestinal wall weakness was suspected when we took into account the period from the onset of bowel obstruction to the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that the location and size of the bezoar have a direct impact on treatment modality, as well as overall success of the attempt [ 4 ]. The endoscopic approach is ideal for favorably sized trichobezoars (i.e., <6 cm) located within or proximal to the stomach [ 4 , 5 ]. Park et al compared clinical outcomes of patients with trichobezoars who underwent endoscopies and found that multiple endoscopic procedures were needed for bezoars greater than 6 cm [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal remains necessary for large trichobezoars and Rapunzel syndrome with extension into the small bowel [ 4 , 6 ]. Case reports exist documenting unsuccessful attempts at endoscopic removal necessitating surgical extraction of the bezoar [ 5 ]. We report the case of a patient with a trichobezoar removed by endoscopy with extubation occurring as a result of the procedure.…”
Section: Introductionmentioning
confidence: 99%